Wavelets for Computer Graphics / Theory and Applications - Derose D. Tony; Salesin H. David; Stollnitz J. Eric (Morgan Kaufmann Publishers, Inc, 1996)
This distinctly accessible introduction to wavelets provides computer graphics professional and researchers with the mathematical foundations for understanding and applying this new and powerful tool. Introduction, Images, HAAR: The Simplest Wavelet Basis, Image Compression, Image Editing, Image Querying, Curves, Subvision Curves, The Theory of Multiresolution Analysis, Multiresolution Curves, Multiresolution Tiling, Surfaces, Surface Wavelets, Surface Applications, Physical Simulation, Variational Modeling, Global Illumination, Further Reading, Appendices, Bibliography, Index.